Um estudo sobre a certificação ISO 9001 no Brasil: mapeamento de motivações, benefícios e dificuldades - Maekawa, Rafael [UNESP]; Carvalho, Marly Monteiro De; Oliveira, Otávio José De [UNESP] (Universidade Federal de São Carlos, 2013)
This work aims to identify the main motivations and difficulties faced by Brazilian companies to obtain ISO 9001 certification. The key quality management practices that provide support to this certification and the relationship with other types of systems, such as ISO 14001 (Environmental Management) and OHSAS 18001 (Occupational Health and Safety Management System), were also investigated. A survey research was conducted with 191 companies. The main motivations for implementing ISO 9001 are the following: internal organization improvement, production efficiency increase, and brand reliability improvement. Employee resistance was the greatest challenge found during the implementation process. On the other hand, the main benefits identified were: quality processes improvement and increased employee awareness of quality. The results reveal that the most common quality programs and tools used are: 5S, brainstorming, and Ishikawa diagram, while the least common are SERVQUAL and QFD.

O objetivo deste trabalho é identificar as principais motivações, benefícios e dificuldades na certificação de Sistemas de Gestão da Qualidade ISO 9001 em empresas brasileiras. Adicionalmente investigaram-se as principais práticas de gestão da qualidade que dão suporte a este tipo de certificação e qual o seu relacionamento com outros tipos de sistemas, tais como a ISO 14001 (Gestão Ambiental) e a OHSAS 18001 (Gestão da Segurança e Saúde do Trabalho). A abordagem metodológica utilizada foi a pesquisa tipo survey, cuja amostra conteve 191 empresas. As principais motivações para implementação da ISO 9001 identificadas foram: possibilidade de melhoria na organização interna, maior eficiência produtiva e maior confiabilidade na marca. A resistência dos funcionários foi apontada como a maior dificuldade. Já os principais benefícios obtidos foram: melhoria da qualidade nos processos e maior conscientização dos empregados em relação à qualidade. Os resultados revelam que os programas e ferramentas da qualidade mais utilizados são: 5S, brainstorming e diagrama de Ishikawa; enquanto os menos utilizados são: o Servqual e o QFD.
Study on ISO 9001 certification in Brazil: mapping the motivations, benefits, and difficulties
Keywords: ISO 9001; Gestão da qualidade; Programas da qualidade; Ferramentas da qualidade; ISO 9001; Quality management; Quality programs; Quality tools